2023
DOI: 10.3389/fgene.2023.1128943
|View full text |Cite
|
Sign up to set email alerts
|

Comparative gonad transcriptome analysis in cobia (Rachycentron canadum)

Abstract: Background: Cobia (Rachycentron canadum) is a species of fish with high commercial potential particularly due to fast growth rates. The evidence of sexual size dimorphism favoring females indicate potential benefits in having a monosex culture. However, the involvement of genetic factors responsible for sexual development and gonadal maintenance that produces phenotypic sex in cobia is largely unknown.Methods: In the present study, we performed transcriptome sequencing of cobia to identify sex-biased significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 95 publications
2
4
0
Order By: Relevance
“…These shared putative TFBSs include Foxl2, Sox3, SF-1, and ESRR, indicating potential roles in gene expression regulation. For instance, Foxl2 has been found to upregulate cyp19a gene expression by directly binding to the promoter in Nile tilapia (Wang et al, 2007), consistent with other studies reporting a female-biased expression of Foxl2 in gonad (Li et al, 2020;Shu et al, 2022;Shen X. et al, 2023). Similarly, we Relative DNA methylation levels in the promoter region of gonad cyp19a for males (blue) and females (pink).…”
Section: Cyp19a Promoter Activation In Vitrosupporting
confidence: 91%
See 1 more Smart Citation
“…These shared putative TFBSs include Foxl2, Sox3, SF-1, and ESRR, indicating potential roles in gene expression regulation. For instance, Foxl2 has been found to upregulate cyp19a gene expression by directly binding to the promoter in Nile tilapia (Wang et al, 2007), consistent with other studies reporting a female-biased expression of Foxl2 in gonad (Li et al, 2020;Shu et al, 2022;Shen X. et al, 2023). Similarly, we Relative DNA methylation levels in the promoter region of gonad cyp19a for males (blue) and females (pink).…”
Section: Cyp19a Promoter Activation In Vitrosupporting
confidence: 91%
“…A sequence spanning approximately 1500bp upstream of the start codon and covering both the first exon and intron, was selected for the analysis. The alignment was conducted with Clustal Omega software (Madeira et al, 2022) and transcription factor binding sites (TFBSs) search was done using JASPAR (Castro-Mondragon et al, 2022) and AnimalTFDB (Shen W et al, 2023) databases. The search was conducted using default parameters, and a minimum relative score of 85% was applied.…”
Section: In Silico Comparative Study Of Scombrids' Cyp19a Promotermentioning
confidence: 99%
“…These shared putative TFBSs include Foxl2, Sox3, SF-1, and ESRR, indicating potential roles in gene expression regulation. For instance, Foxl2 has been found to upregulate cyp19a gene expression by directly binding to the promoter in Nile tilapia (Wang et al, 2007), consistent with other studies reporting a female-biased expression of Foxl2 in gonad (Li et al, 2020;Shu et al, 2022;Shen X. et al, 2023). Similarly, we Relative DNA methylation levels in the promoter region of gonad cyp19a for males (blue) and females (pink).…”
Section: Cyp19a Promoter Activation In Vitrosupporting
confidence: 91%
“…Furthermore, the co-transfection of Foxl2 with SF-1 was shown to have a synergetic influence in the in vitro activation of cyp19a promoter, effect lost when the promoter is hypermethylated (Navarro-Martıń et al, 2011). Likewise, Sox3 has also been found to be differentially higher expressed in females (Li et al, 2020;Shen X. et al, 2023) and is suggested to affect cyp19a transcription by directly binding to the promoter in a frog species (Oshima et al, 2009). The presence of these common regulatory elements across scombrids suggests a conserved regulatory network governing gene expression.…”
Section: Cyp19a Promoter Activation In Vitromentioning
confidence: 99%
See 1 more Smart Citation